2016
DOI: 10.1186/s13568-016-0216-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous crossbreeding of sake yeasts using growth selection systems for a-type and α-type cells

Abstract: Sake yeasts belong to the budding yeast species Saccharomyces cerevisiae and have high fermentation activity and ethanol production. Although the traditional crossbreeding of sake yeasts is a time-consuming and inefficient process due to the low sporulation rates and spore viability of these strains, considerable effort has been devoted to the development of hybrid strains with superior brewing characteristics. In the present work, we describe a growth selection system for a- and α-type cells aimed at the cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The plasmids also carry drug-resistance markers, which allow for the selection of hybrids. Fukuda et al (2016) describe another approach for selecting diploid cells with either an a or α mating type. In their technique, a / α diploid cells are transformed with a plasmid carrying either the a 1 or α 2 gene from the mating-type locus together with drug-resistance markers with promoters specific to either the a 1 or α 2 gene products.…”
Section: Hybrid Generationmentioning
confidence: 99%
“…The plasmids also carry drug-resistance markers, which allow for the selection of hybrids. Fukuda et al (2016) describe another approach for selecting diploid cells with either an a or α mating type. In their technique, a / α diploid cells are transformed with a plasmid carrying either the a 1 or α 2 gene from the mating-type locus together with drug-resistance markers with promoters specific to either the a 1 or α 2 gene products.…”
Section: Hybrid Generationmentioning
confidence: 99%
“…LOH is a natural event that generates homozygous loci via chromosomal rearrangement in heterozygous loci (Daigaku et al, 2004;Alvaro et al, 2006;Andersen et al, 2008;Takagi et al, 2008). Although the spontaneous frequency of LOH is below 1 9 10 À4 as reported in previous studies (Hiraoka et al, 2000;Fukuda et al, 2016), it is higher than that of a point mutation, approximately 1 9 10 À6 (Hayashi and Umezu, 2017). After cultivating strain BY4743C without cerulenin, we isolated homozygous cells generated from heterozygous cells via LOH of the FAS2 using 25 lM cerulenin (Fig.…”
Section: By4743-4c4mentioning
confidence: 85%
“…Sake is a traditional Japanese alcoholic beverage made from fermented rice, and sake yeast strains have many characteristics suitable for brewing, such as aromatic production and high ethanol tolerance (Katou et al, 2008). A previous study (Fukuda et al, 2016) has reported that K9 strain maintains a neardiploid DNA content, which was measured using FACS analysis after propidium iodide-staining. Unexpectedly, only homozygous cells were generated via recombination of the FAS2 gene in K9 strain (Fig.…”
Section: By4743-4c4mentioning
confidence: 99%
“…MATa/a or MATα/α diploids generated through artificial mating type conversion are easily isolated from the cell population since the abundance ratio of target cells in the cell population reaches much beyond 20% by preventing autopolyploidization [36]. The mating type of the isolated cells can be identified by a mating assay using a and α tester strains [82][83][84]. Hybrid tetraploid strains are generated through cocultivation of MATa/a and MATα/α diploids derived from different strains, and selected from the cell population by using marker genes on episomal vectors introduced into each parental strain.…”
Section: Artificial Mating Type Conversion Using the Ho Endonucleasementioning
confidence: 99%
“…However, it is difficult to convert mating types of yeast strains with stuck mutation at the MAT gene as described above. Recently, the MAT gene of haploid cells was successfully substituted with a synthetic DNA containing MATa or MATα, through homologous recombination [84]. Mating type alteration of yeast cells was performed by suppressing the mating ability of parental cells in the same manner shown in Figure 7.…”
Section: Conversion Of the Mat Gene In Haploid Cellsmentioning
confidence: 99%